Time-optimal trajectory planning for excavators operating arm based on SA-PSO algorithm - ZHANG Yunyue; ZHAO Zhicheng; YANG Kai; ZHANG Yu; YANG Jiangtao (Jixie chuandong)
ObjectiveIn view of the problems of unstable operation, low optimization efficiency and falling into local optimum when optimizing the operation trajectory with a single intelligent algorithm, this paper proposes to combine simulated annealing and particle swarm optimization (SA-PSO) to perform optimal time planning for the excavation task trajectory of the excavator operating arm.MethodsFirstly, in the D-H coordinate system, the mechanism diagram of the excavator operating arm is constructed to establish its kinematic model; secondly, the 4-3-3-3-4 piecewise polynomial is used for interpolation, and the SA-PSO algorithm is used to optimize the high-efficiency excavation task trajectory under the constraints of joint velocity and acceleration; finally, under the same operation task, the differential evolution algorithm (DE) and particle swarm optimization algorithm (PSO) are used in turn to obtain the time optimal trajectory.ResultsThe experimental results show that the optimal time trajectory obtained by the hybrid algorithm has shorter operation efficiency and the smallest impact, which can effectively reduce the wear of each joint hydraulic cylinder. At the same time, the hybrid algorithm takes the least time to obtain the optimal trajectory, which helps to improve the real-time performance of the excavator operating arm in actual engineering operations. Furthermore, in order to verify the feasibility of the planned trajectory, the optimization results were substituted into the physical verification, and the results showed that the optimized trajectory achieved efficient and smooth operation of the excavator operating arm.